KETERLIBATAN TURKI DALAM RUNTUHNYA REZIM BASHAR AL-ASSAD DI SURIAH TAHUN 2024 - Husna, Rafika; Saeri, Mohammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The Kurdish movement in the Middle East exploited the conflict in Syria to gain de facto autonomy in northern Syria through the formation of the Democratic Union Party (PYD) and its military wing, the YPG (People's Protection Units of Kurdistan). This group then formed the Syrian Democratic Forces (SDF), affiliated with the Kurdistan Workers' Party (PKK) in southeastern Turkey and supported by the United States. This poses a threat to Turkey, as the PKK has long waged an insurgency in Turkey and threatened Turkish sovereignty. This research employed qualitative methods through a case study approach and library research as its data collection technique. In analyzing Turkey's involvement in the collapse of the Bashar al-Assad regime, this study utilizes an offensive realism perspective to describe Turkey's aggressive stance in securing its national interests in Syria through a proxy war to overthrow the regime. The results of this study indicate that Turkey was indirectly involved in the collapse of the Bashar al-Assad regime in Syria in 2024, using its latent power. This latent power takes the form of a proxy war by supporting the SNA and HTS in an effort to bring down the Bashar Al-Assad regime. Turkey also provided territorial protection to HTS in Idlib before they launched an attack on November 24-December 8, 2024. In addition, Turkey provided military assistance such as light combat vehicles, ammunition, and intelligence information to HTS and SNA. Not only that, Turkey also helped conduct diplomacy and discussions with countries allied with the Assad regime to refrain from retaliatory attacks when HTS launched an attack on December 8, 2024. In the economic sector, Turkey provided logistical assistance in the form of food and medicine, and even helped facilitate alternative trade routes for HTS to maintain their financial stability. Therefore, Turkey played a major role in the collapse of the Bashar Al-Assad regime in Syria in 2024. Keywords: HTS and SNA, Turkish involvement, proxy war, offensive realism, Bashar Al-Assad regime